Creative Thinking Process and Brain Dominance: Divergent and Convergent Thinking in Originality and Elaboration - Bayu Sukmaangara; Muhamad Gani Rohman (MASI Mandiri Edukasi, 2025)
The creative thinking process results from the interaction between divergent and convergent thinking, which complement each other and are influenced by brain hemisphere dominance in processing information. The emphasis on originality and elaboration in this process demonstrates that each individual possesses unique problem-solving tendencies, making them worthy of focus in educational research. This study aims to describe the processes of divergent and convergent thinking in mathematical creative thinking, with a focus on originality and elaboration based on brain dominance. The research method employed was qualitative, with a descriptive and exploratory approach. The sample consisted of 3 students, selected for in-depth analysis from a total of 31 students. The instruments used were mathematical creative thinking, brain dominance tests, and unstructured interviews. Data were analyzed through data reduction, presentation, and conclusion. The study's results showed that students with left-brain dominance relied more on convergent thinking processes when solving problems. Conversely, students with right-brain dominance tend to prioritize divergent thinking. Students with balanced brain dominance showed a relatively balanced ability in using both thinking patterns. These findings provide educators with an overview of how to design questions that encourage thinking processes involving both divergent and convergent thinking, tailored to students’ brain dominance, to optimize learning outcomes.